Food Security as a Social Determinant of Health: Tackling Inequalities in Primary Health Care in Spain - Mireia Campanera; Mercè Gasull; Mabel Gracia-Arnaiz (Harvard FXB Center for Health and Human Rights, 2023)
Food insecurity can be understood as a manifestation of health inequality and thus a deprivation of the right to health. This paper explores the strategies followed in primary health care centers in Spain to care for people struggling to regularly access healthy, safe, and sufficient food. Ethnographically based, our study analyzes, on the one hand, the resources available to primary health care teams to assess the social determinants of health and, on the other, the importance that professionals give to food in the diagnosis, treatment, and prevention of diseases related to inequality. Given that our study was carried out during the recent economic and health crises, the results show the difficulties faced by these centers in responding to constantly changing social needs. Budget cuts, a lack of specific or structural actions, and the invisibilization of particular expressions of inequality have proven challenging to the aim of providing integrated care capable of recognizing the environmental factors that condition patient health. In the case of food insecurity, our study found that there are no instruments in primary care centers to identify and therefore address this insecurity. We explore whether this is due mainly to the growing lack of means or more to the fact that the relationship between material living conditions, food, and health has been downplayed-and the responsibility of the health system in guaranteeing the right to food correspondingly diluted.